Assessing the impact of a potential canine vaccine for the control of Chagas disease: a mathematical modeling study - Edem Fiatsonu; Aniruddha Deka; Martial L. Ndeffo-Mbah; Martial L. Ndeffo-Mbah (Frontiers in Tropical Diseases)
IntroductionChagas disease, a zoonotic infection transmitted by triatomine bugs, poses serious public health risks in endemic areas. As dogs are important reservoirs in the disease’s spread, developing a canine vaccine could be transformative for controlling disease transmission to dogs and humans.MethodsWe developed a compartmental Susceptible-Infected model to simulate the transmission dynamics of Trypanosoma cruzi, considering interactions among dogs, humans, cats, rodents, and triatomine vectors. We used the model to assess the direct and indirect impacts of two vaccine mechanisms—all-or-nothing and leaky—on disease incidence across different host populations. The sensitivity of the model’s outcomes to changes in input parameters was analyzed using univariate sensitivity analysis.ResultsOur model showed that with a 90% vaccine efficacy, an all-or-nothing vaccine could reduce the cumulative incidence of T. cruzi in dogs by 91.3% over five years. The 60% and 30% vaccine efficacies would result in reductions of 63.47% and 33%, respectively, over 5 years. Similarly, the leaky vaccine achieved a 92.62% reduction in dog infections over 5 years with 90% efficacy. The indirect effects on human T. cruzi infection were notable; the all-or-nothing vaccine reduced human disease incidence by 14.37% at 90% efficacy, while the leaky vaccine achieved a 32.15% reduction over 5 years. Both vaccine mechanisms may substantially reduce T. cruzi incidence among dogs, and generate indirect benefit to other hosts, such as humans, by reducing their infection risk. The indirect benefits of vaccination were heavily influenced by the proportion of triatomine bugs blood meals taken from dogs.DiscussionThe study highlights the potential of targeted canine vaccination in controlling Chagas disease transmission and burden in endemic countries. It provides additional evidence for pursuing the development of a canine vaccine as a valuable tool for Chagas disease elimination.